Public Art as City Symbol: Legal Challenges in Copyright and Moral Rights Protection - Hendrico Dolok; Hulman Panjaitan; Andrew Betlehn (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Intellectual property protection for public art installations presents a complex legal challenge when such works evolve into recognizable urban icons. This research aims to analyze the legal safeguards provided to creators of public artworks under the framework of Law Number 28 of 2014 and to evaluate the application of the principle of legal certainty in the